Preoperative, Perioperative, and Pathological Characteristics of Sigmoid, Rectosigmoid, and Upper Rectal Adenocarcinomas: A Retrospective Cohort Study from the Turkish Colorectal Cancer Database. - Benlice, Çiğdem; Moniri, Ariorad; Ramoğlu, Nur; Bağda, Makbule Ayşegül; Baca, Bilgi; Group, Turkish Colorectal Cancer Database Study (Turkish Journal of Colorectal Disease, 2026)
Aim This retrospective cohort study used the Turkish Society of Colon and Rectal Surgery Colorectal Cancer Database to compare the preoperative clinical characteristics and 30-day postoperative outcomes of patients undergoing curative surgery for adenocarcinomas of the sigmoid colon, rectosigmoid junction, and upper rectum. Method Patients who underwent curative resection for non-metastatic adenocarcinoma of the sigmoid colon, rectosigmoid junction, or upper rectum between January 2017 and January 2025 were identified. Tumors ≥10 cm from the anal verge were classified as upper rectal cancers. The three anatomical groups were compared regarding clinical parameters, 30-day outcomes, and histopathology. Statistical comparisons were performed using the chi-squared or Fisher's exact tests for categorical variables and the t-test or Mann-Whitney U test for continuous variables. Results A total of 634 patients were analyzed [sigmoid: 274 (43.3%), rectosigmoid: 174 (27.4%), upper rectum: 186 (29.3%)]. Patients with sigmoid cancer were older (mean 64±12 years) with a higher proportion of women (42%) than those with rectosigmoid and upper rectum cancer (p-value <0.001). Magnetic resonance imaging use was significantly higher in upper rectal tumors (73%) than in rectosigmoid (11%) and sigmoid (0%) tumors. Neoadjuvant therapy was administered to 62% of upper rectal and 11% of rectosigmoid tumors but only 4% of sigmoid tumors (p-value <0.001). Stage III disease occurred more frequently in rectosigmoid (40%) and upper rectum (55%) cancer than in sigmoid (32%) cancer (p-value <0.001). Lymph node positivity was highest in the upper rectum (57%). Conclusion Significant differences in diagnostic workup and treatment strategies exist across these segments. Rectosigmoid tumors share oncologic characteristics with rectal tumors but are often managed as colonic cancers, highlighting the need for clearer anatomical definitions and treatment guidelines.